Fenomena Judi Online : Faktor, Dampak, Pertanggungjawaban Hukum - Bakhtiar, Septu Haudli; Adilah, Azizah Nur (Universitas Pahlawan Tuanku Tambusai, 2024)
The advancement of technology has influenced the structure and culture of life, leading to human adaptation to a constantly changing environment, including the rampant increase in online gambling. Digitalization has facilitated easy access through smartphones, with transactions reaching Rp. 104.42 Trillion in October 2023, despite government closure of online gambling sites, new platforms have emerged. Influencers also promote online gambling on their social media platforms. Online gambling violates the law under Pasal 27 (2) of the 2024 UU ITE , with penalties of up to 6 years in prison and/or fines of up to 1 billion rupiah, yet arrests of perpetrators have been made, the access trend remains high, causing serious economic and psychological impacts. This research analyzes legal norms using a normative juridical approach, including the driving factors of online gambling, its impacts, and the legal accountability of perpetrators, which harm individuals and society at large, increasing criminality and disrupting mental health. Countermeasures involve raising awareness about the dangers of online gambling, enforcing strict law enforcement, and cross-sector cooperation to block transaction access, emphasizing the need for legal awareness and stronger preventive actions to address the proliferation of online gambling.